Commercially pure titanium via wire arc directed energy deposition using localised shielding - Aruntapan Dash; Victor K. Champagne; Amit Bandyopadhyay (Philosophical Magazine Letters, 2025)
Powder-based additive manufacturing (AM) of commercially pure titanium (CPTi) presents challenges regarding feedstock handling, surface oxide formation, and limited build volume. This study examines the microstructural, mechanical, and crystallographic properties of wire arc-directed energy deposition (WA-DED) CPTi specimens utilising a novel localised shielding technique. Implementing a high-purity argon purging system effectively mitigated oxide formation during the printing process. X-ray diffraction analysis revealed a preferential crystallographic orientation along the (002) plane, with a consistent α-titanium phase. Residual stress measurements significantly reduced from 203.53 MPa in as-printed specimens to 17.02 MPa after heat treatment. Microstructural examination showed serrated and acicular α-grains with an average size of 22 μm. Microhardness and tensile testing revealed mechanical properties comparable to those of Grade 3-Ti, with a ductile failure mechanism. The research highlights the potential of the advanced localised shielding technique in enhancing the quality of large-scale additively manufactured titanium components.